2005
DOI: 10.1136/jcp.2005.027623
|View full text |Cite
|
Sign up to set email alerts
|

Survey of clinical allergy services provided by clinical immunologists in the UK

Abstract: Background: The UK National Health Service is failing to meet the need for diagnosis and treatment of allergic disorders, which are common and increasing in prevalence. The House of Commons select committee report on allergy services highlighted the inequalities and urgent need for investment. Aim: To survey the allergy workload provided by clinical immunologists to inform service planning and resource allocation. Results: The immunology centres surveyed serve 32 million people and offer almost the complete re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Testing for allergen‐specific IgE is carried out currently in approximately 100 UK laboratories, whose workload varies from 5000 to 50 000 tests/year [9]. Each laboratory can choose from a repertoire of about 800 allergen preparations available as panels or individual allergens (depending upon the manufacturer) falling into the following major subgroups: (a) spores and pollens, (b) foods, (c) insects and mites, (d) venoms, (e) animal proteins, (f) drugs and (g) occupational allergens.…”
Section: Total and Specific Ige Testingmentioning
confidence: 99%
“…Testing for allergen‐specific IgE is carried out currently in approximately 100 UK laboratories, whose workload varies from 5000 to 50 000 tests/year [9]. Each laboratory can choose from a repertoire of about 800 allergen preparations available as panels or individual allergens (depending upon the manufacturer) falling into the following major subgroups: (a) spores and pollens, (b) foods, (c) insects and mites, (d) venoms, (e) animal proteins, (f) drugs and (g) occupational allergens.…”
Section: Total and Specific Ige Testingmentioning
confidence: 99%
“…Work has also been undertaken to describe the core competencies required by GPs to provide allergy care and those which might be needed to provide a specialized level in primary care (general practitioner with a special interest, GPSI) . GPSIs are generally GPs who work part‐time in a defined clinical role, for example they see about 7% of allergy referrals in the UK . It is of note that one of the consequences of this skill and knowledge deficit is many unnecessary referrals to specialist clinics and recourse to complementary and alternative medicine .…”
mentioning
confidence: 99%
“…45 A study carried out in the UK has shown that immunologists, who have formal training in allergy, provide allergy care to 32 million individuals in the UK. 46 Some authors have pointed out that immunologists are indeed the sole providers of allergy services in parts of the UK. 44 46 Other specialists such as those with primary qualifications in ENT, respiratory medicine or dermatology also contribute to the delivery of allergy services in many countries 3 including about 10% of the total secondary care for allergy in the UK.…”
Section: Resultsmentioning
confidence: 99%